Foreign corrupt practices act compliance guidebook : protecting your organization from bribery and corruption - Biegelman, Martin T.; Biegelman, Daniel R. (Wiley corporate F & A, 2010)
Foreign Corrupt Practices Act Compliance Guidebook shows readers how the Foreign Corrupt Practices Act (FCPA) has grown to critical importance to any U.S. company that does business in a global environment, as well as foreign companies that supply or have agency agreements with U.S. companies